The influence of hofstede’s cultural dimensions on corporate social responsibility implementation: a study on state-owned companies in Java, Indonesia - Erlina Diamastuti; Tyas Ajeng Nastiti; Marisya Mahdia Khoirina (The Indonesian Accounting Review, 2020)
This study aims to examine the influence of Hofstede’s cultural dimension on the implementation of Corporate Social Responsibility at State-Owned Companies in Java, Indonesia. The data were analysed using multiple linear regression analysis with the sample consisting of 100 employees at 50 state-owned company in Java, Indonesia taken by using a purposive sampling method and the return rate of the questionnaire is 62%. The results indicate that the five dimensions of Hofstede’s culture only Power Distance and Individualism/ Collectivism have a positive and significant effect on the implementation of Corporate Social Responsibility by State-Owned Companies in Indonesia, while Uncertainty Avoidance, Masculinity/ Femininity and Long-term/ Short-term Orientation have a negative but not significant effect on the implementation of Corporate Social Responsibility. The results also indicate that not all of Hofstede’s cultural dimensions affect the implementation of corporate social responsibility to state-owned companies in Java, Indonesia. This research is expected to provide benefits for researchers and the community that culture is one of the factors that can be considered as a component that can influence the implementation of Corporate Social Responsibility.